The Current Condition of Coral Reef and Fish Diversity in Gosong Island, Southwest Aceh - Nurul Najmi; Ananingtyas S. Darmarini; Nanda Muhammad Razi; Mai Suriani; Samsul Kahar (Jurnal Ilmiah Perikanan dan Kelautan, 2023)
Highlight Research The current condition coverage percentage of coral reefs in the waters of Gosong Island was 55% Percentage of dead coral with algae founded on Gosong Island is 28% On Gosong Island there are 11 families, namely Acroporidae, Agariciidae, Faviidae, Fungiidae, Merulinidae , Mussidae, Dendrophylliidae, Oculinidae, Pectiniidae, Pocilloporidae and Poritidae Abstract The coral reef ecosystem is an important ecosystem; its existence has a very close relationship with the surrounding ecosystem and the reef fish community. The direct and indirect dependence of reef fish on coral reefs has become an important issue at the national and international levels. This study aimed to determine the characteristics of coral reef ecosystem conditions, the percentage of coral growth, identify the types of coral reefs, and the diversity of reef fish species on Gosong Island, Southwest Aceh. Coral reef biophysical characteristics were collected by measuring water quality, calculating the percentage of coral coverage using the Point Intercept Transect (PIT) method, and the abundance of reef fish using the Underwater Fish Visual Census (UFVC) method. The condition of average percentage of coral reefs in the waters of Gosong Island was in a good category (55%), found as many as 31 genera of hard corals included in the line transect. The percentage of base substrate that dominates other than live coral is dead coral with algae (DCA) of 28%. The average abundance of reef fish in Gosong Island waters is 11,260 ind/ha with an average reef fish biomass of 2074,095 kg/yield. The water quality results show good conditions for coral growth in location. Based on the analysis of the structure of the fish community found in the coral reef area, the results showed good results, so the research location became a good habitat for various types of fish associated with coral reef ecosystems on Gosong Island